2012
DOI: 10.1091/mbc.e12-08-0619
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of G3BP coupled with efficient translation inhibits stress granules in Semliki Forest virus infection

Abstract: Semliki Forest virus nsP3 sequesters G3BP to inhibit stress granule formation on viral mRNAs. Furthermore, the efficient translation of viral mRNAs containing a translation enhancer element assists disruption of SGs in infected cells. This work thus describes a novel mechanism for SG disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
254
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(270 citation statements)
references
References 43 publications
13
254
3
Order By: Relevance
“…1A). We did not observe the persistence of TIA-1-positive SGs in SFV-⌬P1ϩ2-infected cells (data not shown) as we had done previously in cells infected with SFV-⌬789, which does not recruit G3BP to viral replication complexes or similar structures (8). These data show that the prolinerich region of SFV was not important for the interaction between nsP3 and G3BP-1 in MEFs.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…1A). We did not observe the persistence of TIA-1-positive SGs in SFV-⌬P1ϩ2-infected cells (data not shown) as we had done previously in cells infected with SFV-⌬789, which does not recruit G3BP to viral replication complexes or similar structures (8). These data show that the prolinerich region of SFV was not important for the interaction between nsP3 and G3BP-1 in MEFs.…”
supporting
confidence: 76%
“…A surprising difference in the findings of the two groups was that the work of Fros and colleagues suggested that the CHIKV nsP3 sequence binding the SH3 domain of amphiphysins (398-PVAPPRRRR-406 [10]) was essential for colocalization of nsP3 and G3BP (9). In contrast to that work, our study showed that the SFV nsP3 C-terminal L/ITFGDFD repeat motifs at positions 449 to 455 and 466 to 472, both well conserved in the Old World alphaviruses (11), were necessary and sufficient for formation of the nsP3/G3BP complex in infected cells (8). Both these regions, although situated within the hypervariable domain (HVD) of nsP3 (12)(13)(14)(15), are highly conserved between both CHIKV and SFV, and it was therefore surprising that the viruses would differ in the region used to bind and recruit G3BP.…”
contrasting
confidence: 61%
See 2 more Smart Citations
“…nsP1 is a methyltransferase and is associated with cellular membranes (4), nsP3 is a phosphoprotein that recruits host factor G3BP and consequently inhibits the formation of cellular stress granules (5,6), and nsP4 is the viral RNA-dependent RNA polymerase (3). nsP2 contains the viral helicase, protease, and a putative C-terminal methyltransferase domain; associates with many host proteins; and can effectively shut down host cell protein synthesis (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%